PENERAPAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DI DESA (Studi Kasus di Kabupaten Lamongan) - Mayowan, Yuniadi (Profit: Jurnal Adminsitrasi Bisnis, 2016)
Information and Communication Technology (ICT) development more and more fast especially in streamlining public service and must reach village level. Beside increasing sercive, ICT has benefit in data processing that is able to be used in development planning, supporting in decision making and others. The goal of this study is to identify the readyness of ICT implementation of human resource, facilities and infrastructure, institutional and budgetting aspects and IT service in village level. Descriptive methode is used and location take place in four villages in Lamongan Regency. Finding is showed the limit number of human resurce who has ICT capability, undistributed of internet network, fulfilled of institutional needs and budgetting support from authorized institution. Finally, information system does not have all service program to serve public and still does not implement in all village government in servicing public.Â Â